CHALLENGES AND DEVELOPMENT WAYS OF DISTANCE EDUCATION IN FOREIGN LANGUAGE TEACHING - Shahnoza B. Abdullayeva (International Journal of Literature and Language Studies, 2026)
this article provides information on methods of teaching foreign languages, problems of distance education, attitudes of teachers and students to modern types of education, advantages and disadvantages of distance education.